Fenomena Oversharing Di Media Sosial: Bentuk Ekspresi Diri Dan Tantangan Privasi Bagi Generasi Z - Lisa Indriani; Trifena Feisa Samola; Thomas Tokan Pureklolon (Professional: Jurnal Komunikasi dan Administrasi Publik, 2026)
The phenomenon of oversharing on social media has become increasingly prominent among Generation Z, who have grown up in an open digital environment. This study aims to understand how oversharing functions as a form of self-expression while simultaneously posing risks to privacy and mental health. The research employs a qualitative descriptive approach through a literature analysis of recent studies on digital identity, online privacy, and self-disclosure behavior. Findings indicate that oversharing often serves as a means of identity formation and social validation in digital spaces. However, this behavior also increases vulnerability to negative consequences such as stress, anxiety, and post-sharing regret. Generation Z tends to overlook long-term privacy risks in favor of short-term social gratification. Thus, oversharing reflects a paradox between the desire for self-expression and the need for privacy protection in the age of social media.